NFM-05. CANCER STEM CELLS PROMOTE RELAPSE IN NEUROFIBROMATOSIS TYPE 1 ASSOCIATED MALIGNANT PERIPHERAL NERVE SHEATH TUMORS. Issue 2 (22nd June 2018) - Sun, Daochun; Sait, Sameer Farouk; Wang, Zilai; Parada, Luis
Abstract: The cancer stem cell (CSC) hypothesis proposes a hierarchy of tumor development, at the apex of which sits a unique set of stem-like cells that are responsible for giving rise to the rapidly proliferating tumor cells and which are the conveyors of drug resistance, tumor spread and reemergence following therapy. Neurofibromatosis type 1 (NF1) associated malignant peripheral nerve sheath tumors (MPNSTs) are malignant sarcomas occurring in 10-15% of NF1 patients. The mortality is high, and approaches 100% in patients with unresectable, metastatic or recurrent disease. Precisely how recurrence occurs is unknown. We developed a transgene, using components of the rat endogenous Nestin promoter and enhancer which contains the herpes simplex virus thymidine kinase gene and GFP (Nes-TK-GFP). This transgene enables labeling of neural stem/neural crest lineage cells plus the ability to specifically eliminate cycling and transgene-expressing cells by ganciclovir (GCV) toxicity. Using an MPNST genetically engineered mouse model (GEMM), we demonstrate that: 1. The transgene is specifically expressed in a subset of MPNST cells that are quiescent (Ki67-;BrdU-); 2. On arrest of tumour cell proliferation with Doxorubicin, pulse-chase experiments demonstrate a tumour re-growth cell hierarchy originating with the Nes-TK-GFP transgene subpopulation; 3. Elimination of the GFP+ cells with chronic GCV administration significantly impeded tumour development and extended survival in allografts and a spontaneous mouse model of MPNST (cis NP;Nes-TK-GFP). Thus, a relatively quiescent subset of endogenous MPNST cells, with properties similar to CSCs, is responsible for sustaining long-term tumour growth through the production of transient populations of highly proliferative cells.